RESEARCH TRENDS IN THE IMPLEMENTATION OF PROBLEM-BASED LEARNING WITH AUDIO-VISUAL MEDIA IN PRIMARY SCIENCE EDUCATION: A SYSTEMATIC LITERATURE REVIEW (2020–2026) - Fartini Damayanti; Tri Joko Raharjo; Nuni Widiarti; Arif Widiyatmoko (Jurnal Cakrawala Pendas, 2026)
Science education in primary schools requires active, contextual, and meaningful learning to develop students’ conceptual understanding and critical thinking skills. Although Problem-Based Learning (PBL) supported by audio-visual media has been widely implemented, existing empirical evidence remains fragmented and has not been comprehensively synthesized. Therefore, this study aims to analyze research trends, implementation characteristics, and research gaps concerning the use of PBL supported by audio-visual media in primary science education during the period 2020–2026. A Systematic Literature Review (SLR) was conducted following the PRISMA 2020 guidelines. Relevant studies were retrieved from Google Scholar and Scopus using predefined search keywords. The articles were screened through identification, screening, eligibility, and inclusion stages based on predetermined inclusion and exclusion criteria, resulting in 22 empirical studies for analysis. Data were synthesized using content analysis and narrative synthesis to identify research trends, implementation patterns, and emerging research gaps. The findings indicate a substantial increase in publications, particularly in 2024. Most studies employed experimental and quasi-experimental designs and primarily focused on learning outcomes and critical thinking. Overall, integrating PBL with audio-visual media consistently enhanced students’ learning outcomes, critical thinking, motivation, and engagement. However, studies investigating implementation processes, teacher readiness, and long-term sustainability remain limited, indicating important directions for future research. This review provides a comprehensive synthesis of current evidence, highlights key research gaps, and offers theoretical and practical implications for researchers and educators in developing more effective and context-sensitive primary science education.